Integrating top-down and bottom-up approaches to understand the genetic architecture of speciation across a monkeyflower hybrid zone - Streisfeld, Matthew; Stankowski, Sean; Chase, Madeline; McIntosh, Hanna (Dryad, 2022)
Understanding the phenotypic and genetic architecture of reproductive
isolation is a longstanding goal of speciation research. In several
systems, large-effect loci contributing to barrier phenotypes have been
characterized, but such causal connections are rarely known for more
complex genetic architectures. In this study, we combine ‘top-down’ and
‘bottom-up’ approaches with demographic modeling toward an integrated
understanding of speciation across a monkeyflower hybrid zone. Previous
work suggests that pollinator visitation acts as a primary barrier to gene
flow between two divergent red- and yellow-flowered ecotypes of Mimulus
aurantiacus. Several candidate isolating traits and anonymous SNP loci
under divergent selection have been identified, but their genomic
positions remain unknown. Here, we report findings from demographic
analyses that indicate this hybrid zone formed by secondary contact, but
that subsequent gene flow was restricted by widespread barrier loci across
the genome. Using a novel, geographic cline-based genome scan, we
demonstrate that candidate barrier loci are broadly distributed across the
genome, rather than mapping to one or a few ‘islands of speciation.’
Quantitative trait locus (QTL) mapping reveals that most floral traits are
polygenic, with little evidence that QTL co-localize, indicating that most
traits are genetically independent. Finally, we find little evidence that
QTL and candidate barrier loci overlap, suggesting that some loci
contribute to other forms of reproductive isolation. Our findings
highlight the challenges of understanding the genetic architecture of
reproductive isolation and reveal that barriers to gene flow aside from
pollinator isolation may play an important role in this system.
Keywords: Barrier traits; quantitative trait locus (QTL); barrier loci; cline; Ecotypes; Mimulus; reproductive isolation; FOS: Biological sciences